Analisi Kelayakan dan Faktor yang Mempengaruhi Produksi Usahatani Padi Sawah Tadah Hujan (Studi Kasus di Desa Bonto Bahari Kecamatan Bontoa Kabupaten Maros) - Nur Indah; Arifin Arifin; Abd. Asis Pata (Universitas Muslim Maros, 2021)
The agricultural sector is still dominant in contributing to the income of a region. Agricultural development, especially food crops, aims to increase production and expand the diversification of agricultural products. This research was conducted in Bonto Bahari Village, Bontoa District, Maros Regency, this research was carried out for 3 months, from January to March 2021, the data method used was quantitative data and multiple regression and the results of this study were the feasibility of rainfed lowland rice farming.